Políticas de inclusão digital pelo viés escolar: algumas evidências de uma experiência brasileira - Roberto de Lima , Márcio; Sousa do Nascimento, Silvania (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This research has as context the digital inclusion of public policies proposed in the projects: "Um Computador por Aluno" (UCA / Brazil ) and “Conectividad Educativa de Informática Básica para el Aprendizaje en Línea" (CEIBAL / Uruguay). It is focused on public school teachers, which was attended by such policies and investigates the possible reconfiguration of pedagogical practices, with a view to teaching appropriation of Digital Technologies of Information and Communication available. The study undertakes a document analysis of the design/creation documents of UCA and CEIBAL and systematized testimonials from teachers. The methodological approach involves content analysis and the development of semantic networks with Atlas.ti. Actually, two case studies are under construction: one in Brazil and another one in the Uruguayan context. This paper presents a preliminary analysis of the Brazilian data, highlights difficulties in the teacher training process and under-utilization of digital technologies.
Keywords: Public Policies; Pedagogical practice; Appropriation; Digital technologies